Synthesis of 2-O-a-D-glucopyranosyl L-ascorbic acid by cyclomaltodextrin glucanotransferase from bacillus sp. - Abd. Rahman, Roshanida (Universiti Teknologi Malaysia, 2006)
Cyclomaltodextrin glucanotransferase (CGTase) [EC 2.4.1.19] was found to catalyze the transglycosylation from α-cyclodextrin (α-CD) to l-ascorbic acid (AA). A main product formed by this reaction was identified as 2-O-α-d-glucopyranosyl l-ascorbic acid (AA-2G) with the enzymatic hydrolysis and ultraviolet absorption spectra using standard AA-2G. A series of maltooligosaccharide substituted 2-O-derivatives of AA were also detected by HPLC. These were thoroughly hydrolized to AA-2G and glucose by treatment with glucoamylase [EC 3.2.1.3]. A large amount of AA-2G was prepared with 500 g of AA and 1000 g of α-CD. Two hundred and fifty grams of purified AA-2G, the content of which was 97%, was obtained through enzyme reactions and purification with HPLC using an ion-exchange resin.